2021
DOI: 10.1016/j.asmr.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The Blackburne–Peel Index for Determining Patellar Height Is Affected by Tibial Slope

Abstract: Purpose: To establish a quantitative relationship between the BlackburneePeel index and posterior tibial slope in both skeletally mature and skeletally immature individuals and to evaluate the rate at which variation in tibial slope influences changes in patellar height categorization as normal, patella alta, and patella baja. Methods: A consecutive series of lateral knee radiographs were retrospectively reviewed. Radiographs were excluded for rotation, inadequate visible proximal tibia length, and obstructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The BPI is influenced by the tibial slope ( Mortensen et al ., 2021 )–increased tibial inclination reduces the BPI values, which is important for its interpretation both in humans and dogs from small breeds.…”
Section: Resultsmentioning
confidence: 99%
“…The BPI is influenced by the tibial slope ( Mortensen et al ., 2021 )–increased tibial inclination reduces the BPI values, which is important for its interpretation both in humans and dogs from small breeds.…”
Section: Resultsmentioning
confidence: 99%
“…These results are, however, based on a simulated supratuberosity ACW osteotomy and account for the CDI only. Although a direct influence of PTS change on the BPI has been established, 37 the reliability of CDI and ISI may also be questioned after a slope-reducing osteotomy. In the current study, a significant postoperative change in FPHI was not identified; there was no influence of delta PTS on delta ( P = .3686) or ratio ( P = .3587) FPHI.…”
Section: Discussionmentioning
confidence: 99%
“…8 The Blackburne-Peel index (BPI) was not used in this study, as it is reported to be directly influenced by changes in the PTS, which may lead to an incorrect assessment of patellar height. 37 Given the concern that changes in PTS could inadvertently influence a tibial referenced technique, the femoral patellar height index (FPHI), a femoral referenced measurement technique, was also measured on frontal radiographs (Figure 4). 27 This index is defined by the ratio of the distance between the tangent line to the medial and lateral femoral epicondyles and the distance between the apex of the patella and the tangent line to the articular surface of the femoral condyles.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the Blackburne-Peel index has been proven to be directly affected by PTS. 35 Described in 2017, the femoral patellar height index is a femur-referenced patellar height measurement method avoiding HTO-related alterations of the proximal tibia. 36 This index could be useful to accurately measure the impact of ACW-HTO on patellar height.…”
Section: Discussionmentioning
confidence: 99%